INVESTIGATING CONSUMER PREFERENCE OF AGENCY BRANCHLESS BANKING (ABB) SERVICE IN INDONESIA - Maulana, Dimas
Indonesia has officially launched Laku Pandai, a policy of Agency Branchless Banking (ABB) service permittance, to assist financial inclusion in Indonesia. Embracing ABB would unlock a new opportunity, a promising untapped market, to reach the unbanked or underbanked who are usually outreached by the conventional or online banking channel. With an investigation of consumer preference, it underlies the fundamental motion of individual likes and dislikes towards an object, that would lead to a predictive behavior of why ABB would be preferred. This understanding would allow marketers to devise a successful marketing strategy. This study has conducted a series of consumer preference research towards ABB in Indonesia. A mixed method approach was conducted in order to grasp a better understanding of the consumer preference. An exploratory qualitative study was conducted in order to identify evaluative criteria factors that would affect consumers evaluation towards making a choice in ABB. This study was conducted in two different regions, which are Ciasihan and Pasar Minggu area. Both of this study represents the successful ABB channel in urban and rural area. A total of 61 respondents were interviewed, with a combination of 25 respondents from Ciasihan, and 31 from Pasar Minggu. Four evaluative criteria factors were identified that affect consumer preferences, which are service, location, perceived safety, and financial benefit. These factors allow a further take of confirmatory study to test the consumer preference in quantitative study. This study tested the consumer preference with two quantitative study, which are MADM analysis and conjoint analysis. Two analysis were conducted to investigate the inherent psychological relationship between individual’s attitude and preference, as well as to take the strength from both analyses. A total of 400 respondents were collected in the quantitative study. MADM analysis allows the investigation of consumer’s attitude towards banking channels, including ATM, ABB, and bank branches. A total of 385 respondents were found to have higher attitude towards ABB channel over ATM and bank branches. ABB was found to have the highest evaluation score in distance attribute, followed by service ease of use, queuing line, error, operational time, and price. Bank branch channel was found to have a higher score in channel safety, but it has no positive overall attitude. Furthermore, a total of 16 combination conjoint profile was also administered in a conjoint survey. Consumers were asked to rank each profile in order to test their ii preference towards ABB service. Closer agent’s distance was found to be the most important attribute that would affect consumer preference towards ABB, followed by transaction price, queuing line, operational hour, and operational day. Two different segmentations were identified through the preference utility, which are distance concern and price concern clusters. Distance concern cluster was found to be dominant with a total of 332 cluster members. This study found that closer ABB distance has been perceived as the most important criteria in consumer preference towards ABB and to be found coherently sound in exploratory qualitative study, MADM analysis, and conjoint analysis. This shows that a geographical convenience would validate the fact that financial exclusion occurs not only in rural, but also urban areas. Besides location, other factors such as price and service were found to affect consumer preference towards ABB over other channels such as ATM and bank branches. These factors provide a basic understanding, but core explanatory that the unbanked or underbanked have different needs from conventional banking. This study also provides an enlightenment of that despite differences between attitude and preference approach domain, the relationship between these two approaches are deductively coherent. With these findings, this study